Sustainable Runggu Strengthening Model: Communal Intellectual Property Protection in Ecotourism Puncak 2000 Siosar, Karo Regency - Amelia Anggriany Siswoyo; Palacheta Subies Subianto (Dinasti Research, 2024)
Runggu is a model of local wisdom of the Karo indigenous community that has an important role in the kinship system, communication and deliberation to make a decision in the Karo indigenous community. Runggu is a collection of